PENERAPAN STRATEGI PENDEKATAN COLLABORATIVE PLANNING PADA POLITEKNIK STIA LAN MAKASSAR - Astriana, Astriana; Irfan, Muhammad (Politeknik STIA LAN Makassar, 2025)
This study aims to see the extent to which the collaborative planning approach has been implemented in improving the quality of planning documents at the STIA LAN Makassar Polytechnic. The background of this study is based on conditions where the process of preparing planning documents is still dominated by a top-down approach. This means that planning is more directed by top-level policies without involving adequate participation from stakeholders at the implementing or beneficiary levels. This study uses a descriptive method with a qualitative approach through interviews, observations and documentation to collect primary and secondary data. The results of this study indicate that the collaborative planning approach has been implemented, but not optimally due to obstacles and problems, such as the process that is still dominated by management and formal planners, while the involvement of lecturers, education staff, and students is not optimal, there is limited time in preparing documents, and the number of functional planner formations that are still not fulfilled. This study offers novelty by examining the application of the collaborative planning approach in the context of government educational institutions, which has received relatively little attention in the public planning literature. The findings of this study not only enrich the theoretical discourse on collaborative planning in the educational bureaucracy, but also provide practical implications in the form of recommendations for strengthening participatory mechanisms, planning governance, and the role of planners as facilitators of collaboration in improving the quality of institutional planning documents.